HUBUNGAN MOTIVASI IBU DENGAN KELENGKAPAN IMUNISASI DASAR ANAK DI WILAYAH KERJA UPTD PUSKESMAS TAMIANG LAYANG - Salasikin, Lela; Dhea Manto, Onieqie Ayu; Latifah, Latifah; Fetriyah, Umi Hanik (Jurnal Delima Harapan, 2024)
Background: Immunisation is one of the cheapest health investments, as it can prevent and reduce the incidence of illness, disability, and death due to Immunisation Preventable Diseases (PD3I). One of the factors for low immunisation rates is the lack of motivation of mothers to bring their children to the posyandu for immunisation. Objectives: Knowing the Relationship between Maternal Motivation and Completeness of Basic Immunisation of Children in the Working Area of UPTD Puskesmas Tamiang Layang. Methods: Analytical Observational Research with cross sectional design. The study population was infants recorded in June - August 2024 in the work area of UPTD Puskesmas Tamiang Layang (posyandu) as many as 54 toddlers. The sample of this study were toddlers aged 9 to 12 months who were taken using accidental sampling technique as many as 48 people. Data collection using a questionnaire. Data were analysed using the chi square test. Results: The majority of respondents with good motivation were 27 people (56.3%) and respondents with complete immunisation status of their toddlers were 29 people (60.4%). Statistical test results using the chi square test showed a p value of 0.000 (<0.05) so it can be concluded that there is a relationship between maternal motivation and child immunisation at UPTD Puskesmas Tamiang Layang. Maternal motivation is causally related to complete basic immunisation because the better the mother's motivation, the mother will provide complete basic immunisation to the baby, but conversely the less the mother's motivation, the mother does not provide complete basic immunisation. Conclusion: There is a relationship between maternal motivation and child immunisation at UPTD Puskesmas Tamiang Layang. Health workers are advised to increase health promotion about immunisation so that mothers have knowledge and increase their motivation to provide basic immunisation to children.